(untitled) (Acta Entomologica Serbica, 2016)
Never recorded before in Serbia, the cynipid gall wasps Aylax papaveris (Perris 1839) and Barbotinia oraniensis (Barbotin 1964) were obtained from capsules of Papaver rhoeas Linnaeus 1753 collected toward the end of June 1998 at the locality Surduk (Srem, Serbia). Nine species of parasitoids were also obtained. Among them were the species Ormyrus capsalis Askew 1994 and Baryscapus papaveris Graham 1991, never before found in Serbia.